Implementation of new technologies in accounting and financial processes: An effectiveness assessment - Rafał Szmajser; Marcin Kędzior; Mariusz Andrzejewski; Katarzyna Świetla (International Entrepreneurship Review, 2022)
Objective: The aim of this paper is to explore accountants’ views on the usage of Robotic Process Automation technology (RPA) which brings efficiency increase.